Clinicopsychological profile of children with bleeding disorders from a tertiary center in Karnataka - Varadarajan, Meera; Rakesh, S R; Ramaswamy, Premalatha; Mohammed, Raj; Ramiah, Smita (Indian Journal of Child Health, 2017)
Objectives: The aim of this study is to observe the clinical spectrum of presentation of hemophilia and other bleeding disorders in children. Material and Methods: This observational study was carried out in the Comprehensive Hemophilia Center at Bangalore Medical College and Research Institute from December 2015 to August 2016. Clinical profile of 126 diagnosed children of hemophilia and other bleeding disorders